2017
DOI: 10.1186/s12884-017-1366-9
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire for assessing breastfeeding intentions and practices in Nigeria: validity, reliability and translation

Abstract: BackgroundValidating a questionnaire/instrument (whether developed or adapted) before proceeding to the field for data collection is important. This article presents the modification of an Irish questionnaire for a Nigerian setting. The validation process and reliability testing of this questionnaire (which was used in assessing previous breastfeeding practices and breastfeeding intentions of pregnant women in English and Hausa languages) were also presented.MethodFive experts in the field of breastfeeding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…The rating of the relevance, clarity, simplicity, and ambiguity of items using four-point scales is something that has been going on for years for content validation [33,43,60,61]. The same parameters were considered for this study.…”
Section: Discussionmentioning
confidence: 99%
“…The rating of the relevance, clarity, simplicity, and ambiguity of items using four-point scales is something that has been going on for years for content validation [33,43,60,61]. The same parameters were considered for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these principles in action can be found in Emmanuel & Clow's (2017) or unwilling to undertake appropriate pre-survey piloting and testing of their online questionnaire, they are strongly advised to consider using an existing robust research tool (Kelley et al 2003).…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…This reflects that the meaning of the items is ascertained but less simple. Similarly, several low values were noted by Emmanuel and Clow's (2017) instrument, but remained in the questionnaire and changes were made based on the participants' feedback. Fortunately, experts in this study suggested changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, items valued 0.78 and beyond remain in the questionnaire. Several studies have exercise CVI test (Sh, Hsu, Toobert., & Wang, 2019) with three to five judges (Emmanuel & Clow, 2017;.…”
Section: Validity: Content Validitymentioning
confidence: 99%